Effects of talc on fire retarding, thermal degradation and water resistance of intumescent coating - Hazwani Dzulkafli, H. (Elsevier Ltd, 2017)
This study presents the influences of talc as an additive in intumescent coating formulations on the thermal insulation, degradation and water resistance. The fire test was performed according to ASTM-E119 standard to study the heat shielding properties of the coated substrates. The results showed that the 20 of the talc enhanced the heat shielding and recorded substrate temperature 75 °C after 100 min of fire test. The morphology of the char was analyzed by Scanning Electron Microscopy (SEM). X-ray fluorescence (XRF), X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) results showed the presence of P2O5, MgO, TiO2, and SiO2 respectively. The functional groups analysis of char confirmed the presence of high temperature compounds and enhanced thermal performance of coatings. Thermogravimetric analysis (TGA) showed that addition of 20 talc increased residual mass of the char by 55.55. The lap shear test result showed that the talc also improved the adhesion of the intumescent coating with steel substrate and the highest shear strength observed was 7 MPa for a formulation, F5 containing 20 talc. Water immersion test was performed according to ASTM D870-15 and the results showed the higher water-resistance was recorded for a formulation containing 10 talc in the control formulation. © 2017 Elsevier B.V.